Testimonial immunity as an institution of criminal procedural law. (Journal of actual problems of jurisprudence, 2016)
Legislative consolidation and improvement of the Institute of witness immunity is a major step towards strengthening the democratic and moral principles of criminal justice. Despite this, the guarantees of this constitutional principle should clearly work. Namely actual participation of counsel in the interrogation of the witness and assigns to him theadditional responsibility to ensure that the rights and legitimate interests of the witness.
Keywords: immunity; witness immunity; the principle of the criminal process; witness advocate